The role of renal function reserve estimation in children with hydronephrosis - Jindal B; Bal C; Bhatnagar V (Wolters Kluwer Medknow Publications, 2007)
Background: Glomerular filtration rate (GFR) is the most widely used indicator of kidney function although it does not invariably reflect the functional status after renal injury. The concept of renal function reserve (RFR) as the ability of the kidney to increase GFR following a protein load was introduced in 1980s. In hydronephrotic children, the acute hemodynamic response to intravenous protein load can cause changes in renal function that are different from changes in normal controls. Materials and Methods: RFR was evaluated in 21 children with hydronephrosis (group I - study group) and in 20 healthy children (group II - control group) by subtracting the baseline GFR from the stimulated GFR following an intravenous protein load. GFR was determined by double compartment-2 plasma sample method using 99m Tc DTPA (diethylenetriamine pentaacetic acid) radioisotope as the filtration agent. Results: The baseline GFR, stimulated GFR and RFR of hydronephrotic children (group I) was found to be significantly lower ( P = 0.01, P = 0.001 and P = 0.03 respectively) as compared with healthy normal children (group II). The stimulated GFR shows a strong correlation with the baseline GFR in both the groups, but the RFR shows a high inverse correlation to the baseline GFR in controls and a very low correlation in study group. Conclusion: RFR is preserved in children with hydronephrosis, but it is reduced in comparison to healthy children. However, its clinical utility to unmask the severity of hydronephrosis is limited by the various limiting factors.